El traspaso de movimientos del tipo de cambio a los precios: Un análisis para la economía Mexicana - Carlos Capistrán; Raúl Ibarra-Ramírez; Manuel Ramos-Francia (Banco de México, 2011)
– This paper analyzes the pass-through of exchange rate to different price indexes in Mexico. The analysis is based on a vector autoregressive model (VAR) using monthly data from January 1997 to December 2010. The pass-through effects are calculated by means of accumulated impulse response functions to a recursively identified exchange rate shock. The results show that the exchange rate pass-through to import prices is complete, but it declines along the distribution chain in such a way that the impact on consumer prices is below 20 percent. Moreover, we find that the exchange rate pass-through seems to have decreased substantially from 2001 onwards, which coincides with the adoption of an inflation targeting regime by Banco de Mexico.
Keywords: E31; F31; F41; 330; exchange rate pass-through; import price; consumer price; distribution chain; inflation; Exchange Rate Pass-Through; Preisindex; Mexiko